2016
DOI: 10.1093/geronb/gbw006
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Personality Traits Preceding Dementia Diagnosis

Abstract: Personality change, specifically an increase in neuroticism, may be an early indicator of dementia. Identification of early indicators of dementia may facilitate development of screening assessments and aid in early care strategies and planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
4
19
0
Order By: Relevance
“…Increased neuroticism seems to be a preceding signal for dementia [ 43 , 93 ] as well as for mild cognitive impairment [ 94 , 95 ]. A study with healthy volunteers (average age 81 years) showed a link between high neuroticism and beta-amyloid deposition in subjects with subjective cognitive complaints [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased neuroticism seems to be a preceding signal for dementia [ 43 , 93 ] as well as for mild cognitive impairment [ 94 , 95 ]. A study with healthy volunteers (average age 81 years) showed a link between high neuroticism and beta-amyloid deposition in subjects with subjective cognitive complaints [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…These were complemented with measures for quality of life and subjective memory complaints as possible subtle consequences of Alzheimer’s pathology as these factors were associated with Alzheimer pathology biomarkers in younger cognitively healthy populations [ 67 70 ]. Furthermore we studied personality traits as they could either be a risk factor for Alzheimer’s dementia or directly influenced by Alzheimer’s pathology [ 41 43 , 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to expectation and a retrospective study (Donati et al, 2013), the group that developed MCI declined slightly on neuroticism, showed no change on extraversion (as compared with controls), and showed no change on conscientiousness (in the article, mean conscientiousness at t3 was mistyped as 2.3 instead of 3; Personal communication, October 2015). One prospective study found change in self-reported neuroticism but not extraversion in 86 octogenarians who received a diagnosis of dementia (Yoneda, Rush, Berg, Johansson, & Piccinin, 2016). Given that this latter study included the assessment at the time of the diagnosis, the increase in neuroticism is likely to have occurred at the time of the diagnosis.…”
Section: Personality Changes and Dementiamentioning
confidence: 99%
“…Likewise, brain-imaging research indicates an age-related association between high neuroticism and smaller regional neural volume, along with greater decreases in brain volume (Jackson et al, 2011), suggesting that neuroticism may contribute to neural degeneration. The existing literature indicates that high or increasing neuroticism is associated with worse cognitive functioning (Boyle et al, 2010;Chapman et al, 2012;Crowe et al, 2006;Graham et al, 2021;Klaming et al, 2017;Meier et al, 2002), cognitive decline (Chapman et al, 2012;Luchetti et al, 2016), dementia (Aschwanden et al, 2021;Duberstein et al, 2011;Johansson et al, 2014;Terracciano et al, 2014;Yoneda et al, 2017Yoneda et al, , 2020, and risk of mortality (Graham et al, 2017;Wilson et al, 2004).…”
mentioning
confidence: 99%